Plasma Jet Synthesis of Cubic Tungsten Carbide of Variable Stoichiometry; Inorganic Materials; Vol. 57, iss. 4 - Sivkov A. A. Aleksandr Anatolyevich; Nassyrbayev (Nasyrbaev) A. Artur; Nikitin D. S. Dmitry Sergeevich; Shanenkov I. I. Ivan Igorevich; Rakhmatullin I. A. Ilyas Aminovich (2021, 2021)
Title screen